Circadian rhythm mechanism in the suprachiasmatic nucleus and its relation to the olfactory system - Tsuno, Yusuke; Mieda, Michihiro (Frontiers in Neural Circuits, 2024)
Animals need sleep, and the suprachiasmatic nucleus, the center of the circadian rhythm, plays an important role in determining the timing of sleep. The main input to the suprachiasmatic nucleus is the retinohypothalamic tract, with additional inputs from the intergeniculate leaflet pathway, the serotonergic afferent from the raphe, and other hypothalamic regions. Within the suprachiasmatic nucleus, two of the major subtypes are vasoactive intestinal polypeptide (VIP)positive neurons and arginine-vasopressin (AVP)-positive neurons. VIP neurons are important for light entrainment and synchronization of suprachiasmatic nucleus neurons, whereas AVP neurons are important for circadian period determination. Output targets of the suprachiasmatic nucleus include the hypothalamus (subparaventricular zone, paraventricular hypothalamic nucleus, preoptic area, and medial hypothalamus), the thalamus (paraventricular thalamic nuclei), and lateral septum. The suprachiasmatic nucleus also sends information through several brain regions to the pineal gland. The olfactory bulb is thought to be able to generate a circadian rhythm without the suprachiasmatic nucleus. Some reports indicate that circadian rhythms of the olfactory bulb and olfactory cortex exist in the absence of the suprachiasmatic nucleus, but another report claims the influence of the suprachiasmatic nucleus. The regulation of circadian rhythms by sensory inputs other than light stimuli, including olfaction, has not been well studied and further progress is expected.